2007
DOI: 10.1161/01.res.0000267856.00713.0a
|View full text |Cite
|
Sign up to set email alerts
|

Role of Krüppel-Like Transcription Factors in Endothelial Biology

Abstract: Abstract-Krüppel-like factors are members of the zinc finger family of transcription factors that have been implicated as playing key roles in regulating cellular differentiation and tissue development. Studies over the past several years support an important role for this family of factors in vascular biology. This review summarizes the role of Krüppel-like factors in endothelial cell biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
317
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 372 publications
(341 citation statements)
references
References 117 publications
9
317
0
3
Order By: Relevance
“…26 KLF2 has multiple binding sites in the promoter of nitric oxide synthase-3 (NOS3), 16,27 which encodes endothelial nitric oxide synthase (eNOS). Previous studies suggest a critical role of eNOS in the progression of kidney disease.…”
Section: Reduced Klf2 Expression Results In Increased Glomerular Endomentioning
confidence: 99%
See 1 more Smart Citation
“…26 KLF2 has multiple binding sites in the promoter of nitric oxide synthase-3 (NOS3), 16,27 which encodes endothelial nitric oxide synthase (eNOS). Previous studies suggest a critical role of eNOS in the progression of kidney disease.…”
Section: Reduced Klf2 Expression Results In Increased Glomerular Endomentioning
confidence: 99%
“…Glomerular hyperfiltration causes shear stress in endothelial cells, 32 which is known to increase KLF2 expression. 26 Recently, we reported that reduced KLF2 expression in endothelial cells leads to more severe glomerular endothelial cell injury and kidney damage in early diabetic nephropathy, which is characterized by glomerular hyperfiltration. 18 However, we were unable to assess the relationship between hyperfiltration and KLF2 expression in diabetic mice, because KLF2 expression is also affected by high glucose and insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Kruppel‐like factor 2 (KLF2) is a zinc‐finger transcription factor preferentially expressed in vascular endothelium, lung, and lymphocytes 1, 4, 5. It functions as a master regulator to maintain endothelial homeostasis5 and control multiple genes critical for anti‐inflammatory, ‐thrombotic, ‐oxidative, and ‐proliferative effects in endothelial cells (ECs) 1, 4, 5, 6, 7, 8, 9, 10.…”
mentioning
confidence: 99%
“…It functions as a master regulator to maintain endothelial homeostasis5 and control multiple genes critical for anti‐inflammatory, ‐thrombotic, ‐oxidative, and ‐proliferative effects in endothelial cells (ECs) 1, 4, 5, 6, 7, 8, 9, 10. For example, KLF2 potently induces the expression of vasodilatory and anti‐inflammatory genes such as endothelial nitric oxide synthase, inhibits vasoconstrictive factors such as endothelin‐1 expression, and represses expression of adhesion molecules, such as vascular cell adhesion molecule 1 (VCAM1) 1, 8, 10.…”
mentioning
confidence: 99%
“…The Kruppel-like family of zinc finger genes is characterized by Cys2-His2 zinc fingers and can be divided further into subsets based on other structural features, including a seven-amino acid H/C link between adjacent fingers and several conserved NH2-terminal modules (19). The PRDM family was first identified when a homologous N-terminal 100-amino acid region (PR domain) was recognized as shared by RIZ (retinoblastoma protein-interacting zinc finger; PRDM2) and the PRDI-BF1/BLIMP1 transcription repressor (PRDM1) that promotes B lymphocyte maturation (20).…”
mentioning
confidence: 99%